2017
DOI: 10.1117/12.2252295
|View full text |Cite
|
Sign up to set email alerts
|

Novel diffuse optics system for continuous tissue viability monitoring: extended recovery in vivo testing in a porcine flap model

Abstract: In reconstructive surgery, tissue perfusion/vessel patency is critical to the success of microvascular free tissue flaps. Early detection of flap failure secondary to compromise of vascular perfusion would significantly increase the chances of flap salvage. We have developed a compact, clinically-compatible monitoring system to enable automated, minimally-invasive, continuous, and quantitative assessment of flap viability/perfusion. We tested the system’s continuous monitoring capability during extended non-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A portion of the results was reported in Refs. 20 and 21. Here, we present findings from the expanded data set.…”
Section: Introductionmentioning
confidence: 91%
“…A portion of the results was reported in Refs. 20 and 21. Here, we present findings from the expanded data set.…”
Section: Introductionmentioning
confidence: 91%
“…The measurements were done on the artery, muscle and skin of the MF in a porcine model but only on two animals. A significant inconsistency in obtained measurements was noted and the authors concluded that further development work is needed 148,149 .…”
Section: Brief Description Of Monitoring Methodsmentioning
confidence: 99%